Guidelines for leveraging university didactics centers to support OER uptake in German-speaking Europe - Ebner, Martin; Schön, Sandra; Kumar, Swapna (Education Policy Analysis Archives, 2016)
Although less well established than in other parts of the world, higher education institutions in German-speaking countries have seen a marked increase in the number of open educational resource (OER) initiatives and in government-supported OER funding in recent years. OER implementation, however, brings with it a unique set of challenges in German-speaking higher education contexts, stemming in part from copyright laws and use permissions that have made sharing and reuse of educational materials less prevalent. The article discusses how instructional development centers, including university didactics centers (hochschuldidaktische Zentren) and e-learning centers, can play a key role in faculty uptake and adoption of OER, and concludes by proposing a set of OER implementation guidelines that leverage the expertise and interfacing role of these centers in German-speaking countries.